Discursive Approaches to Ambiguous Loss: Theorizing Community‐Based Therapy After Enforced Disappearance. Issue 3 (September 2016) - Robins, Simon
Abstract: Ambiguous loss is experienced and constructed relationally. As a result, the social and political context plays a role alongside psychological factors as elements that both mediate the impact of ambiguous loss and can aid or retard effective coping. By considering the case of persons disappeared in political violence, an approach to addressing ambiguous loss is theorized that uses community‐based therapeutic approaches. Beginning from poststructuralist ideas of discourse as being constitutive of human subjectivity, the role of discourse is discussed in terms of its capacity to both construct ambiguity and mold social relations that can build resilience. A therapeutic approach is postulated with families of the disappeared that seeks explicitly to have an impact on discourses circulating in communities affected by disappearance in ways that positively influence the well‐being of the families of those missing, as well as on the meanings and identities that affected persons construct from them.